The Use of Local Language as an Intercultural Communication Model in K-Pop Fanbase - Mutiara Syifa Amartya Rachman; Iis Kurnia Nurhayati (Budapest International Research and Critics University, 2022)
The Covid-19 pandemic requires human especially in Indonesia to carry out Work from Home (WFH) and maintain distance between individuals. With the occurrence of WFH, resulting in human dependence on the internet. On the other hand, this dependence on the internet is really being used by the Kpop (Korean Pop) Industry to further strengthen its existence in Indonesia. This was marked by the official presence of the SM Entertainment representative office in Jakarta. SM entertainment then brought NCT in 2019 to take over the Indonesian market by presenting content about Indonesia. Therefore, this study aims to discuss how NCT applies this intercultural communication to their market in Indonesia and how the role of the Indonesian language used by NCT can strengthen loyalty and enlarge its fanbase. The theory used in this research is the Intercultural Communication Model theory from Gudykunst and Kim. In-depth interviews were conducted using qualitative case study methods, which resulted in question indicators from the Intercultural Communication Model such as culture, socio-culture, psycho-culture and the environment. The results of the study stated that the Intercultural Communication Model according to Gudykunst and Young was applied in the communication between NCT and these fans. Culture, Socio-culture, and Psychoculture are the most effective approaches to communicate with Indonesian fans. NCT's communication through Indonesian culture and language also affects the tourism aspect which increases NCTzens as domestic tourists who visit places that NCT has visited while in Indonesia as the effect of their loyalty as NCTzens.